Effect of adiponectin level and genetic variation of its receptors on diabetic retinopathy: A case–control study - Liao, Wen-Ling (Medicine (Baltimore), 2019)
Adiponectin (APN) and its receptors have been reported to be associated with metabolic phenotypes. To better understand the effects of APN levels and its receptors on diabetic retinopathy (DR), we investigated the association of the plasma APN level and variations in APN-related genes with DR, individually and in combination. Patients with type 2 diabetes (T2D; N = 1604), above 20 years of age from the Taiwanese population participated in the study. Demographic information, blood pressure, and serological markers were recorded at enrollment. Genomic DNA was isolated and genotyped. The plasma APN levels were measured by enzyme-linked immunosorbent assay. T2D patients with DR (N = 632) had diabetes for a longer duration, and had higher HbA1c, and systolic and diastolic blood pressure compared to those without DR (N = 972) (P < .001, for all the parameters). Overall, 10 single nucleotide polymorphisms (SNPs) in ADIPOQ and CDH13 susceptibility loci were associated with DR. Gene risk score (GRS) was calculated based on 10 SNPs for each subject and the cumulative effect of genes was observed. Among the subjects with plasma APN level (N = 518), natural logarithm (LN) of APN (LN [APN]; odds ratio [OR] = 1.63, 95% confidence interval [CI] = 1.19–2.25) and GRS (OR = 1.90, 95% CI = 1.11–3.26 for middle range of GRS, and OR = 2.61, 95% CI = 1.48–4.59 for high range of GRS) were independent risk factors for DR after adjustment for other parameters. In conclusion, the plasma APN level and the genetic variations in adiponectin receptors were associated with DR.